AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN, BATANG DAN BUAH LABU SIAM (Sechium edule (Jacq.) Swartz) DENGAN METODE 2,2-DIFENIL-1-PIKRILHIDRAZIL (DPPH) DAN CUPRIC REDUCING ANTIOXIDANT ACTIVITY (CUPRAC) - Ayu Kusumaningrum, Dian
Free radicals are compound or molecule which have one or more unpaired electrons. Free radicals in the body can damage the unsaturated fatty acids in the cell membrane, resulting brittle in cell walls and often lead to many kinds of diseases such as atherosclerosis, degenerative diseases, and cancer. Antioxidant are used to prevent oxidation and protect cells from free radical attack. The human body has natural antioxidant such as glutathione, but this is not enough to scavenge all of the free radical reactions that occur in the body so it was need addition of antioxidant from the outside. Cucurbitaceae family had been proved as having antioxidant activity. The objectives of this research were to determine the antioxidant activity of the leaves, stems, and fruit chayote (Sechium edule) by determining IC50 of DPPH scavenging activity and EC50 of CUPRAC capacity, total phenolic, flavonoid and carotenoid content, their correlation with the IC50 DPPH and EC50 of CUPRAC, and correlation between IC50 DPPH and EC50 of CUPRAC. Extraction was performed by reflux apparatus using three solvents with increasing polarity, namely n-hexane, ethyl acetate and ethanol. Extracts were monitored by thin layer chromatography (TLC). IC50 DPPH, EC50 CUPRAC, total phenolic, flavonoid, carotenoid content of each extract was conducted by ultraviolet-visible spectrophotometry, and their correlation with IC50 DPPH and EC50 CUPRAC, correlation between IC50 DPPH and EC50 CUPRAC using Pearson?s method. The highest antioxidant activity was showed by the lowest IC50 DPPH (1.27 µg/mL) which was given by ethyl acetate pedicel extract of chayote and the lowest EC50 CUPRAC by ethyl acetate fruit extract of chayote (147.09 µg/mL). The highest of total phenolic, flavonoid, and carotenoid content were exposed by ethyl acetate fruit extract, ethyl acetate leaves extract, and ethyl acetate leaves extract which were 3.21 g GAE/100 g, 11.64 g QE/100 g ,and 12.73 g BE/100 g, respectively. Total phenolic content in fruit extract of chayote had negatively high correlation with IC50 DPPH value. Total phenolic, flavonoid carotenoid content in fruit and pedicel extracts of chayote had negative and high correlation with EC50 CUPRAC. DPPH scavenging activities of leaves, fruit and pedicel extract of chayote had no positive correlation with their CUPRAC capacities. All of ethyl acetate and ethanol leaves, fruit, and pedicel extracts were categorized as very strong antioxidant by DPPH method. Antioxidant activity of leaves extract of chayote by DPPH method might be predicted indirectly by determining total phenolic content. Phenolic compounds were the major contributor in antioxidant activity of leaves extract of chayote by DPPH method. CUPRAC and DPPH methods gave no linear result in antioxidant activity of leaves, fruit and pedicel extracts of chayote.